STUDI MENGENAI PENGARUH KEPERCAYAAN MEREK TERHADAP KEPUTUSAN PEMBELIAN JASA PENDIDIKAN PASCA SARJANA (Studi Kasus Program Pascasarjana Magister Manajemen Universitas Diponegoro Semarang) - Ariwidodo, Bagus (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2009)
The reseach about affected on brand trust to buying decision has been done by manyresearchers. This research was conducted to analyze factors, that influence on buying decision. The research problem which proposed in this research is how to improve decision of buying. To answer the question, the research has developed a model and fout hypotesis has proposed in the reseach.Sample used in this research are 100 responden. They are student of Program PascasarjanaMagister Manajemen Diponegoro University, term 30, 31, 32, and 33.The data analysis used in this research is Structural Equation Modeling (SEM) in AMOS 7,0 program.The result of SAM analysis complete the Goodness of Fit Index criteria namely: Chi Square 107.633, probability 0,283, RMSEA 0,028, GFI 0,885, AGFI 0,843, TLI 0,988, CFI 0,990, CMIN/DF 1,076.Result of the analysis tells that four hypothesis are accepted, H1 : Advertising positively and significantly affecting Perception of Quality, H2 : Advertising positively and significantly affecting Brand Trust, H3 : Perception of Quality positively and significantly affecting Brand Trust, H4: Brand Trust positively and significantly affecting buying decision.